Game-Driven Learning in the Digital Age: A Systematic Review and Meta-Analysis - et. al., Larisa V. Mezentseva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Learning is the base human need. We are living in a modern and mobility world which require more and more changes and in the study process especially. The knowledge has to be deeper and more special, but it’s getting process has to be invert – more quickly and ease. This article considers the educational aspects in the Digital age which are based on games. Games play a significant role in the process of keeping a new knowledge. The contemporary time proposes specific possibilities for existing entertainment activity for study. The aim of the article is to investigate the condition of education in the era of digital technologies, in particular, with references to the lessons based on the gaming practice. The methodological basis of the research consists of systematic methodology, method of interpretation, analytical method, comparative and generalizing methods and meta-analytical method. It is very important to explore this phenomenon as long as game study in the 21 century becomes a new alternative for education and, in general, a qualitative stage of development.